The Influence Of Board Of Directors’ Characteristics On Corporate Social Responsibility Disclosures In Jordanian Islamic Banks - Murad Ali Ahmad Al-Zaqeba; Suhaila Abdul Hamid; Omar M. Shubailat; Baker Akram Falah Jarah; Fawwaz Ali Taha Ababneh; Zeyad Almatarneh (Institute of Advanced Science Extension (IASE), 2024)
Volume 10, Issue 11 (November 2023), Pages: 1-13